Transforming Growth Factor-Beta and Matrix Metalloproteinases: Functional Interactions in Tumor Stroma-Infiltrating Myeloid Cells - Jelena Krstic; Juan F. Santibanez (The Scientific World Journal)
Transforming growth factor-beta (TGF-β) is a pleiotropic factor with several different roles in health and disease. In tumorigenesis, it may act as a protumorigenic factor and have a profound impact on the regulation of the immune system response. Matrix metalloproteinases (MMPs) are a family that comprises more than 25 members, which have recently been proposed as important regulators acting in tumor stroma by regulating the response of noncellular and cellular microenvironment. Tumor stroma consists of several types of resident cells and infiltrating cells derived from bone marrow, which together play crucial roles in the promotion of tumor growth and metastasis. In cancer cells, TGF-β regulates MMPs expression, while MMPs, produced by either cancer cells or residents’ stroma cells, activate latent TGF-β in the extracellular matrix, together facilitating the enhancement of tumor progression. In this review we will focus on the compartment of myeloid stroma cells, such as tumor-associated macrophages, neutrophils, and dendritic and mast cells, which are potently regulated by TGF-β and produce large amounts of MMPs. Their interplay and mutual implications in the generation of pro-tumorigenic cancer microenvironment will be analyzed.